Fabrication and characterization of a Pt/MgxZn1−xO/ZnO Schottky barrier photodiode utilizing a field plate structure. (23rd February 2018) - Endo, Haruyuki; Takahashi, Kyo; Kashiwaba, Yasube
Abstract: We fabricated a Pt/Mg x Zn1− x O/ZnO Schottky barrier photodiode (SBPD) utilizing a field plate structure and investigated the characteristics of its electric property toward realization of a high-gain avalanche photodiode for feeble ultraviolet ray detection. A Mg x Zn1− x O film on the Zn-face of a c -ZnO substrate was grown by the plasma-assisted MBE method. The fabricated Pt/Mg x Zn1− x O/ZnO SBPD showed a low reverse current and a high breakdown voltage of −380 V, and several SBPDs showed high breakdown voltage in excess of the measurement limitation of −500 V. The high breakdown voltage was achieved by a low density of defects in both the Mg x Zn1− x O film and ZnO substrate and the field plate structure, and therefore a depletion layer reached the bulk of the ZnO substrate through the Mg x Zn1− x O film.